Targeting LSD1 in tumor immunotherapy: rationale, challenges and potential - Bao, Lei; Zhu, Ping; Mou, Yuan; Song, Yinhong; Qin, Ye (Frontiers in Immunology, 2023)
Lysine Specific demethylase 1 (LSD1) is an enzyme that removes lysine methylation marks from nucleosome histone tails and plays an important role in cancer initiation, progression, metastasis, and recurrence. Recent research shows that LSD1 regulates tumor cells and immune cells through multiple upstream and downstream pathways, enabling tumor cells to adapt to the tumor microenvironment (TME). As a potential anti-tumor treatment strategy, immunotherapy has developed rapidly in the past few years. However, most patients have a low response rate to available immune checkpoint inhibitors (ICIs), including anti-PD-(L)1 therapy and CAR-T cell therapy, due to a broad array of immunosuppressive mechanisms. Notably, inhibition of LSD1 turns "cold tumors" into "hot tumors" and subsequently enhances tumor cell sensitivity to ICIs. This review focuses on recent advances in LSD1 and tumor immunity and discusses a potential therapeutic strategy for combining LSD1 inhibition with immunotherapy.